Lending Operations of the International Monetary Fund - Bourneuf, Alice (The Review of Economics and Statistics, 1946)
THE International Monetary Fund has supervision over the exchange rate and exchange control policies of members and also provides financial assistance to members. importance of its supervision of exchange rate and exchange control policies is generally recognized; opinions differ, however, on the importance of its lending operations. Mr. Nurkse has said, The main function of the International Monetary Fund will be to create an addition, and quite a substantial addition, to aggregate international liquidity. 1 Mr. Viner, discussing the original Keynes and White plans, said, By creating an additional and flexible supply of internationally liquid means of payments both plans would provide needed safeguards against either world or local deflations originating in national balance of payment difficulties. This is the greatest service which the plans would render . . .n2 present paper examines the contribution which the Fund's lending operations may make to international monetary stability and the avoidance of deflationary and restrictive measures. Reasonable stability and freedom in international monetary relations are possible only if appropriate measures are taken to achieve balance over a period of time in the international transactions of individual countries. adoption of suitable exchange rate and exchange control policies is of fundamental importance. But if unnecessary changes in exchange rates, excessive restrictions on current transactions, and domestic deflationary measures are to be avoided, it is perhaps of equal importance that countries have some available means of meeting balance of payments deficits. From this point of view the Fund's lending operations may be considered as important as its supervision of exchange rate and exchange control policies. Although the Fund has the power to object to exchange rate changes and exchange controls on current transactions, it can not do so in practice unless there are some other means of meeting the deficit or correcting the situation.